Mekes – Creating an Imagery of Kingship and Transmission of power in Ancient Egypt - Arab, Walid Shaikh Al (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The mekes was an important element of the royal ceremonial regalia. Started from the reign of the First Dynasty’s pharaoh Den (2914—2867 BC), the mekes was frequently depicted in reliefs, where the pharaoh grasps it in his raised left hand with the -flail in the other, while performing a ritual race during his coronation’s ceremonies. The aim of the present article is to build upon the analysis included in previous studies, to propose an accurate translation for this object and its meaning, and to demonstrate its political and socio-religious connotations communicated by its iconography. After a survey of previous studies, the question of its name will be briefly tackled, and an analysis of its attestations will be presented. However, given the largess of potential data sources, we have delimited the survey to the inscriptions of Edfu temple as a sample to the Ptolemaic and Roman temples.